isolasi dan karakterisasi protein hemaglutinin sub unit pill Salmonella typhi=Isolation and Characterization of Hemaglutinin Protein Sub Unit Pili Salmonella typhi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
The aim of the research was to isolate and characterize hemaglutinin protein sub unit pili as a virulence factor of Salmonella typhi. The characterization was done in two steps. The first step was a hemaglutination test to find out the molecular weight of hemaglutinin protein sub unit pili. The second step was to analyze antibodies against protein hemaglutinin sub unit pili by Western blot method and the inhibitory activities of the antibodies on the adherent test. The test was carried out in two ways, by blocking the enterocytes with hemaglutinin protein and blocking pili of S. typhi with antibodies against hemaglutinin protein sub unit pili. The adherence test between S. typhi and rat intestinal enterocytes was done as a control. The molecular weight of hemaglutinin protein sub unit pili was 20 kDa. Antibodies against hemaglutinin protein sub unit pili 20 kDa showed a cross reaction with 38, 30, and 16 kDa sub unit pili. Both pretreatment of the enterocytes with hemaglutinin protein pili and pretreatment of the bacteria S. typhi with antibodies against hemaglutinin protein sub unit pili could inhibit the adherence of the S. typhi on rat intestinal enterocytes. It can be concluded that S. typhi hemaglutinin protein sub unit pili has the molecular weight of 20 kDa and plays an important role in the adherence mechanism of S. typhi on rat intestinal enterocyte.